Book Clubs as a Pedagogical Tool for Developing Critical Thinking: Evidence from an English Education Program in Indonesia - Rusiana Rusiana; Nuraeningsih Nuraeningsih; Titis Sulistyowati; Muh. Syafei; Farid Noor Romadlon; Agung Dwi Nurcahyo; Loreen P. Agulan; Natthanan Thongmark; Sibhekinkosi Anna; Havva Kurt-Taşpınar; Abdurrahman Ahmed Milad (Universitas Muhammadiyah Surakarta, 2024)
In higher education, critical thinking skills are essential for students to develop their ability to explore problems, questions, or situations, find a solution, and justify their positions. Such skills can be cultivated through sustained, authentic dialogue with peers or in groups. To provide a supportive environment for dialogue and interaction among students, a book club was utilized as an alternative and extension activity of Extensive Reading course within the English Education Study Program at a private university in Indonesia. The book club enables students to connect with others, expressing and exchanging ideas and thoughts, thereby sharpening their critical thinking skills. This mixed-method study investigated the students’ reading and critical thinking skills after participating in the book club, the effectiveness of book club in developing these skills, and the ways in which the book club fostered critical thinking skills. Twenty-three freshmen from one class participated in the study. The instruments used were a reading test, a survey of critical thinking skills, and students’ work. The reading test and critical thinking survey were administered sequentially after the treatment, while students’ work was qualitatively analyzed. The findings reveal that book club is effective in developing student’s critical thinking skills, particularly in terms of creating alternative t endings to a given story.